Effects of Stable Vagus Nerve Stimulation Efficacy on Autistic Behaviors in Ten Pediatric Patients With Drug Resistant Epilepsy: An Observational Study - Wang, Zhiyan; Yuan, Xing; Zhang, Qian; Wen, Jialun; Cheng, Tungyang; Qin, Xiaoya; Ji, Taoyun; Shu, Xiaomei; Jiang, Yuwu; Liao, Jianxiang; Hao, Hongwei; Li, Luming; et al. (Frontiers in Pediatrics, 2022)
Vagus nerve stimulation (VNS) is a safe and effective therapy for pediatric patients with drug-resistant epilepsy (DRE). However, in children with DRE, the effects of VNS on autistic behaviors remain controversial. We retrospectively collected data from ten children with DRE who underwent VNS implantation and regular parameter regulation in three pediatric epilepsy centers, and completed the behavioral assessments, including the autistic behavior checklist and the child behavior checklist, at follow-ups 1 (mean 2.16 years) and 2 (mean 2.98 years). The ten children maintained stable seizure control between the two follow-ups. Their autistic behaviors, especially in language, social and self-help, were reduced at follow-up 2 compared to follow-up 1 (p=0.01, p=0.01, respectively). Moreover, these improvements were not associated with their seizure control, whether it was positive or negative. These results suggested that the VNS might have a positive effect on autistic behaviors, which provided a clinical basis of VNS for DRE pediatric patients with autism spectrum disorder (ASD).